Ingestive behavior of supplemented Nellore heifers grazing palisadegrass pastures managed with different sward heights. (9th September 2016) - Vieira, Bruno Ramalho; Azenha, Mariana Vieira; Casagrande, Daniel Rume; Costa, Diogo Fleury Azevedo; Ruggieri, Ana Cláudia; Berchielli, Telma Teresinha; Reis, Ricardo Andrade
Abstract: Three sward heights (15, 25 and 35 cm) and three supplement types (energy, energy‐protein, and a mineral mix supplement) were evaluated in a 3 × 3 factorial arrangement distributed in a completely randomized design to study changes in forage search patterns in Nellore heifers in a continuous grazing system. Pasture data were collected using two replicates (paddocks) per treatment over four periods during the rainy season. The behavior assessments were made in the first and fourth grazing seasons. It was hypothesized that supplements and pasture management would modify ingestive behavior, considering that animals would require less time grazing if they had energy requirements met through higher digestibility of better managed paddocks, or use of supplements high in energy. Total and green forage masses along with green : dead material ratio were greater in treatments managed with higher sward heights. Sward managed with 35 cm height resulted in lower leaf : stem ratio compared with 15 cm sward height treatments. The animals on the 15 cm pastures spent more time grazing overall and during each meal, but there were no differences observed in meal numbers in comparison to 35 cm treatments. Heifers fed protein and/or energy supplements spent less time grazing in the early afternoon, but overall grazing time was the same for all animals.